Bibliometric visualization of metal-air battery research trends - Pinandita, Satria; Asnawi, Rustam; Syamsiro, Mochamad (Institute of Advanced Engineering and Science, 2025)
Metal-air batteries are rechargeable secondary batteries with high energy density, typically using carbon electrodes. However, carbon waste poses environmental risks. Fly ash, a byproduct of coal combustion, offers a sustainable alternative due to its high electrical conductivity. This study analyzes research trends on metal-air batteries and fly ash from 2019 to 2023 using bibliometric visualization of Scopus-indexed publications. The keyword search was refined from 'Battery' to 'Air Battery' and, finally, 'Air Battery' with 'Fly Ash,' yielding 60 relevant articles. Using the VOSviewer, research patterns, key focus areas, and collaboration networks were identified. The results indicate a 14.87% increase in publications from 2019 to 2023, with significant growth from 2019 to 2021 before declining after 2022. This fluctuation suggests shift in research interests toward other battery technologies. Fly ash demonstrates potential as a carbon substitute for air batteries, promoting sustainability. However, further research is needed to optimize its application and address technical challenges. Bibliometric visualization highlights a growing interest in fly ash for environmentally friendly battery development due to its abundance and sustainability.